2016
DOI: 10.1088/0031-8949/t167/1/014006
|View full text |Cite
|
Sign up to set email alerts
|

Development of tungsten fibre-reinforced tungsten composites towards their use in DEMO—potassium doped tungsten wire

Abstract: For the next step fusion reactor the use of tungsten is inevitable to suppress erosion and allow operation at elevated temperature and high heat loads. Tungsten fibre-reinforced composites overcome the intrinsic brittleness of tungsten and its susceptibility to operation embrittlement and thus allow its use as a structural as well as an armour material. That this concept works in principle has been shown in recent years. In this contribution we present a development approach towards their use in a future fusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
93
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(96 citation statements)
references
References 21 publications
2
93
0
1
Order By: Relevance
“…Furthermore, studies regarding the mechanical response and plastic deformation at elevated temperatures showed that the wire can keep its valuable properties [26,27]. Additionally, some investigations dealt with the question of the effect of annealing on tensile properties of pure [28] and potassium doped tungsten wire [29], interconnecting in such a way general microscopic features to different material responses occurring in the experiment.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, studies regarding the mechanical response and plastic deformation at elevated temperatures showed that the wire can keep its valuable properties [26,27]. Additionally, some investigations dealt with the question of the effect of annealing on tensile properties of pure [28] and potassium doped tungsten wire [29], interconnecting in such a way general microscopic features to different material responses occurring in the experiment.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it is generally recognized that WK is a metal matrix composite because the non-alloyable constituent K, is almost insoluble in W. The K bubble in W is recognized as the strongest pinning phase at high temperatures against the migrations of GBs and dislocations [51]. The excellent performances of the WK filaments at high temperatures make people associate them with the possible applications in nuclear fusion installations [16, 19, 24, 25, 31, 32, 38, [55][56][57][58][59][60][61][62][63]. On the basis of summarizing the previous research work, this paper briefly reviews WK performances including mechanical properties, the resistance to thermal shock, and irradiation tolerance.…”
Section: Pfms and Wkmentioning
confidence: 99%
“…WK wires which displayed good ductility and high strength at high temperatures were used as a reinforced phase to enhance mechanical performances. Literature [57] showed that K-doped W wires could enhance the overall operating temperature and the allowed fabrication temperature of the W-based composite. W-fiber (containing K, W f )-reinforced composites could show pseudo-ductility even at RT.…”
Section: Mechanical Properties Of Wkmentioning
confidence: 99%
“…This is the case for tungsten fibers in an 'asfabricated condition' [11]. Thermal treatment during the production of the composite or through operation conditions of the fusion reactor and additional embrittlement due to neutron irradiation can reduce the ductility of the tungsten fibers [12].…”
Section: Tungsten Fiber-reinforced Tungsten (W F /W)mentioning
confidence: 99%